THE IMPORTANCE OF FORUM ANAK KOTA YOGYAKARTA (FAKTA) IN ACCOMMODATING YOGYAKARTA CHILDRENâS PARTICIPATION - , RADEN RORO RETNO WIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This graduating paper aims to give brief information about a children forum in Yogyakarta Forum Anak Kota Yogyakarta (FAKTA) and to describe the functions and agendas of FAKTA in order to accommodate children participation rights. The methods of collecting data are direct observation, interview, and library research. Direct observation is conducted when I became its general treasure during 2009-2012 period. Interviews are conducted with the chief of FAKTA and its staffs, the staff of Office of Societies and women empowerment (KPMP), as the advisor of FAKTA. Meanwhile, library research is done to collect some additional information to support the discussion of this paper. In conclusion, FAKTA is one of the children forums which accommodate children participation rights, and the only children forum which is facilitated by the government of Yogykakarta through KPMP. The activities of FAKTA, which involve children around Yogyakarta, make this forum important to accommodate children participation rights.